Penerapan Model Disconvery Learning untuk Meningkatkan Keaktifan Belajar Siswa pada Materi Ekosistem Kelas X SMAN 6 Mataram - Kurniawati, Lindra Wahyu; Yasa, I Komang Mudika; Artayasa , I Putu (IKIP Siliwangi Bandung, 2023)
Education in schools in the learning process can create quality human resources in keeping up with the times. The implementation of learning requires an effective, creative, and innovative learning model to optimize the learning process by increasing student learning activity, one of which is by applying the Discovery Learning model. The purpose of this study is the application of the Discovery Learning model to increase student learning activity in the class X ecosystem material of SMAN 6 Mataram. This research method uses the type of Classroom Action Research (PTK) which is carried out with the subject of research, namely grade X8 students with a total of 34 even semesters of the 2022/2023 academic year at SMAN 6 Mataram. Data collection techniques use observation sheets with assessment rubrics, field notes and documentation. The results showed that the implementation of learning increased from the average of cycle I of 65% (medium category) to the average of cycle II of 78% (high category). The implementation of learning by inserting games makes students actively learn, dare to answer questions, do assignments and express opinions, so that learning strategies must be applied according to the learning needs and characteristics of students.